HPB P31 Early Postoperative Anthropometric and Nutritional Measures Correlate with Fitness for Adjuvant Chemotherapy after Pancreatoduodenectomy. (7th December 2022) - Halle-Smith, James; Carnegy, Alasdair; Loo, Joan; Roberts, Keith
Abstract: Background: Adjuvant chemotherapy (AC) improves survival after pancreatoduodenectomy (PD) for periampullary cancer. Unfortunately, not all PD patients are fit for AC, and it is likely that perioperative malnutrition plays a role. Therefore, the aim of this study was to investigate the relationship between early postoperative anthropometric and nutritional measures with fitness for adjuvant chemotherapy after PD. Methods: All patients undergoing PD for periampullary cancer between 2018–2020 at our institution were reviewed. Those who were referred for AC were included in the study and split into two groups: those who received AC and those who were not fit enough to receive AC. Demographic, perioperative, anthropometric, nutritional and outcome measures were compared between the two groups. Results: 66 patients were suitable for inclusion in the study, of which 15 (23%) were not fit for AC. Overall survival was significantly greater in the AC group (29.7 months vs. 16.7 months; p=0.037). Body mass index (BMI) was similar between the groups at admission but during inpatient stay dropped significantly more in the no-AC group (-1.34 kg/m2 vs. -0.10 kg/m2; p=0.035). BMI was also significantly lower at first follow-up (3–4 weeks after surgery) in the no-AC group (20.2 kg/m2 vs. 25.2 kg/m2; p=0.018). Albumin was similar between the two groups on admission and discharge. However, at first follow-up albumin was significantly lower in the no-AC group (31 g/L vs. 38 g/L; p=0.019). There was no difference in postoperative complications between the two groups. Conclusions: BMI and albumin in the early postoperative period appear to be significantly related to fitness for adjuvant chemotherapy. By routinely measuring these values and intervening in those struggling with nutrition postoperatively before their first Oncology appointment, it may be possible to increase the proportion of patients fit enough to receive AC, and thus improve survival after PD. BMI and albumin have some limitations so future work should concentrate on more reliable measures such as body composition measures.